Phonological performance measured by speech severity indices compared with correlated factors - Wertzner, Haydée Fiszbein; Amaro, Luciana; Santos, Daniela Evaristo dos (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Some factors seem to influence speech impairment among phonologi- cally disordered children. The aim was to compare severity indices with some correlated factors. DESIGN AND SETTING: Observational, analytical and cross-sectional study conducted within the Language-Speech-Hearing Sciences Course, Universidade de São Paulo. METHOD: Fifty phonologically disordered chil- dren with ages ranging from 4 to 11 years took part. The indices were calculated from phonology tests and were correlated with anamnesis and au- diological data. Student’s t test and Spearman’s correlation were used to compare percentages of consonants correct (PCC) and process den- sity index (PDI) for children with and without otitis, upper respiratory histories and audio- logical abnormalities, with regard to whether or not they were comprehended during assessment, their ages when they started to speak and their ages at the assessment. RESULTS: The higher the age at the assessment was, the higher the PCC (imitation: 0.468; naming: 0.431; Spearman’s correlation) and the lower the PDI (imitation: 0.459; naming: 0.431); the later the child started to speak, the lower the PCC (imitation p = 0.064; naming p = 0.050) and the higher the PDI (imitation p = 0.067; naming p = 0.042). There were differences between groups with and without upper respiratory history (PCC: imitation p = 0.016, naming p = 0.005; PDI: imitation p = 0.014, naming p = 0.008). There was no difference between the groups regarding otitis, comprehension during the assessment and audiological data. CONCLUSIONS: Children with upper respiratory histories who began to speak later presented more severe speech impairment indices.